HYPERKINETIC CONDUCT DISORDER PADA ANAK USIA DINI - Shinta Brisma; Dian Budianti Amalina; Rivani Kurniawan (Yayasan Nusantara Hasana Berdikari, 2026)
Hyperkinetic Conduct Disorder (HCD) is a severe neurodevelopmental disorder characterized by the coexistence of pervasive inattention, marked hyperactivity–impulsivity, and persistent conduct disturbances. This disorder represents a more severe clinical spectrum of attention-deficit/hyperactivity disorder accompanied by conduct disorder and is associated with significant impairment in cognitive, social, and emotional functioning. Children with early-onset HCD are at high risk of academic failure, interpersonal conflict, and progression to more severe behavioral or personality disorders in adolescence and adulthood. This case report describes a 4-year-old girl presenting with chronic hyperactivity, impulsivity, emotional dysregulation, self-injurious behavior, and delayed speech development. Comprehensive psychiatric evaluation revealed severe hyperactivity, impaired social functioning, and maladaptive behavioral patterns consistent with Hyperkinetic Conduct Disorder (F90.1) according to the Indonesian Classification of Mental Disorders (PPDGJ-III). The patient was managed using a multimodal treatment approach combining pharmacological therapy and structured psychosocial interventions. Early identification and comprehensive management of Hyperkinetic Conduct Disorder are crucial to improving long-term outcomes, preventing progression to more severe psychopathology, and supporting optimal developmental trajectories in affected children.